Grit dan Self-Control pada Mahasiswa Fakultas Kedokteran - Jesslyn Antoinette Justine; Ellen Theresia (Humanitas (Jurnal Psikologi), 2019)
This research was conducted with the aim of knowing the relationship between grit and self-control which is a variable that can predict the lecture process and achievement. The study was conducted on 114 active students of the "X" Faculty of Medicine. The results of the calculation of correlation with the Spearman correlation method obtained correlation results of 0.531, meaning that there is a moderate, positive and significance relationship between grit and self-control in the 2015 Medical Faculty Students. The conclusion of this study is that there is a moderate relationship between grit and self-control. The researcher suggests that further researchers can conduct this research on respondents in other faculties, as well as gather further data regarding external and internal disorders that affect self-control. Keywords: grit, self control, college student